Proposed study designs for approval based on a surrogate endpoint and a post-marketing confirmatory study under FDA's accelerated approval regulations for disease modifying osteoarthritis drugs. Issue 4 (April 2019) - Kraus, V.B.; Simon, L.S.; Katz, J.N.; Neogi, T.; Hunter, D.; Guermazi, A.; Karsdal, M.A.
Summary: In 1992, the Food and Drug Administration (FDA) instituted the accelerated approval regulations that allow drugs or biologics for serious conditions that fill an unmet medical need to be approved on the basis of a surrogate endpoint or an intermediate clinical endpoint. The current definition of a serious condition includes chronic disabling conditions, such as osteoarthritis (OA), and thereby provides expanded opportunities for the use of biomarkers for regulatory approval of drugs for OA. The use of surrogates or intermediate clinical endpoints for initial regulatory approval of a drug or biologic requires confirmation in a post-marketing study of a drug effect on a clinically relevant outcome, such as on how a patient feels, functions or survives. Current FDA guidance requires that the post-marketing approval (PMA) study be ongoing during the time of initial drug approval. This white paper arose out of the need to brainstorm trial designs that might be suitable for PMA of drugs initially approved, on the basis of a surrogate or intermediate clinical endpoint, for treatment of OA to alter disease progression, abnormal function or pathological changes in the morphology of the joint. In this white paper we define the concept and regulations regarding accelerated approval and propose two major study design scenarios for PMA trials in OA. The long-term goal is to discuss and refine these designs in consultation with regulatory agencies in order to facilitate development of drugs to fill the large unmet need in OA.